1996
DOI: 10.1007/bf01875571
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mevalonate metabolism in the sea bass (Dicentrarchus labrax L) liver

Abstract: The activities of mevalonate kinase, mevalonate 5-phosphate kinase and mevalonate 5-pyrophosphate decarboxylase, were examined in sea bass (Dicentrarchus labrax L) liver. The activities of the three enzymes were studiedin vitro in relation to the influence of protein content, time of incubation, pH, temperature, mevalonate, ATP and Mg(++) concentration. Protein content in the assay medium affected the three enzymes differently. Mevalonate kinase, mevalonate 5-phosphate kinase, and mevalonate 5-pyrophosphate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Richard et al (2006) and Peng et al (2008) reported that European seabass and black seabeam fed diets containing vegetable oils showed a lower cholesterol content compared to fish fed a fish oil diet. Whereas, other studies (Dannevig and Norum, 1982; Estévez et al, 1996; Gilman et al, 2003) have shown that the presence of phytosterol in vegetable oils can affect absorption and metabolism of cholesterol in fish.…”
Section: Resultsmentioning
confidence: 94%
“…Richard et al (2006) and Peng et al (2008) reported that European seabass and black seabeam fed diets containing vegetable oils showed a lower cholesterol content compared to fish fed a fish oil diet. Whereas, other studies (Dannevig and Norum, 1982; Estévez et al, 1996; Gilman et al, 2003) have shown that the presence of phytosterol in vegetable oils can affect absorption and metabolism of cholesterol in fish.…”
Section: Resultsmentioning
confidence: 94%
“…The hypocholesterolaemic effect of SBM compared with FM is well documented in fish ( 2 , 9 ) . At present, information on cholesterol metabolism in fish is limited ( 35 ) . Blood cholesterol level is the result of dietary cholesterol (exogenous cholesterol) and de novo cholesterol synthesis in the liver (endogenous cholesterol).…”
Section: Discussionmentioning
confidence: 99%
“…1.1.33). Studies of all these enzymes have been reported from sea bass 169 and an enzyme assay has been developed for all three. 170 These enzymes (and those involved in subsequent formation of farnesyl pyrophosphate) are associated with the peroxisomes.…”
Section: Eukaryotes 21 Biosynthesis Of Isopentenyl Pyrophosphate From...mentioning
confidence: 99%